"My life only happened on the Internet": Pedro’s case in the perspective of Merleau-Ponty’s phenomenology - Saraiva, Francisco Raone Barbosa; Souza, Camila; Moreira, Virginia (Estudos e Pesquisas em Psicologia, 2022)
The Internet has changed our relationship with time and also transformed experiences, developing new forms of subjectivation. In contemporary society, individuals are increasingly connected, which can lead to addictions such as Internet gaming disorder. This is related to one of the dimensions that underlies human existence: time. This work aims to understand, from the view of Merleau-Ponty’s philosophical phenomenology, the experience of the lived time of Pedro, a young man dependent on Internet gaming. We use the single case study as a method, and we understand Pedro’s addiction to Internet gaming as a phenomenon linked to the relationships established between him and the contemporary world, whether in the individual or collective sphere. These relationships are inseparable from the elements that make up Pedro’s Lebenswelt (lifeworld), such as temporality. The time of the clock influenced the internal time and vice versa, denoting the indivisibility of the phenomenon inwhich there is only a sense of time because man is time itself.